PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) BERDASARKAN PERINGKAT PROPER DI RSUD UNGARAN - Bella Arieza Andriyana; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The hospital is one of the agencies that must perform the assessment for PROPER, this is because it has risks in water pollution, air pollution, and the management of B3 waste generated from health service activities in the hospital. RSUD Ungaran is a type C hospital that has not received PROPER assessment in B3 waste management. The management is still not in accordance with Government Regulation No. 101 in 2014, Health Minister Decision No. 1204 in 2004, Environment and Forestry Minister No 56 in 2015 and Environment Minister Decision 03 in 2014. The purpose of this research is to know the management of Hazardous and Toxic Waste based on PROPER rate in RSUD Ungaran. This research is a qualitative research with cross sectional approach. The sample uses a total sampling technique consisting of 3 main informants and 1 triangulation informant. The results showed that the source of the waste came from 14 hospital service rooms with the volume of B3 waste produced per day average of 91.65 kg/day. Assessment of waste management related to sorting, storage, and transportation got percentage of 57,1% which mean still less than requirement that is 100%. The result of PROPER assessment get red rating with percentage 32,26%.